Social exclusion in South American criminal justice systems: AP-RIMES, preliminary results - Prado Manrique, Bertha (My University, 2021)
RIMES is a comparative instrument, validated by international experts, capable of measuring the social exclusion generated by the rules and practices of the criminal justice systems on suspects, defendants, convicted and ex-convicted persons. This instrument has been applied to evaluate the criminal policies of countries in Europe and North America. The aim of this presentation is to explore the applicability of this instrument to measure the social exclusion generated by the South American penal systems. The preliminary results of its application to two Andean countries, Chile and Peru, show, on the one hand, that the RIMES can be applied to evaluate the penal systems of these countries. On the other hand, they also show the need to delve into some of the socially exclusive dynamics of South American criminal policy through the design of a specific sub-instrument for the region.
Keywords: América del Sur; Derecho penal; Exclusión social; South America; Criminal policy; Social exclusion; RIMES; Penal System